Evidence that the pregnane X and retinoid receptors PXR, RAR and RXR may regulate transcription of the transporter hOCT1 in chronic myeloid leukaemia cells. (31st July 2014) - Austin, Gemma; Holcroft, Alison; Rinne, Natasha; Wang, Lihui; Clark, Richard E.
Abstract The expression and activity of the uptake transporter human organic cation transporter 1 (hOCT1; SLC22A1) is an independent predictor of response to imatinib treatment in patients with chronic myeloid leukaemia (CML). We have recently shown that peroxisome proliferator‐activated receptor (PPAR) activation can increase the killing effect of imatinib in CML cells, due to upregulated hOCT1 gene expression and increased imatinib uptake. To investigate the role of activation of nuclear receptors other than PPAR in the transcriptional regulation of hOCT1, CML cells were treated with agonists for 13 adopted orphan receptors and endocrine receptors. It was found that hOCT1 expression was upregulated by the agonists for pregnane X receptor (PXR), retinoid acid receptor (RAR) and retinoid X receptor (RXR) in CML cell line and primary CML cells (P = 0.04; Wilcoxon rank test). Hence, agonists for PXR, RAR and RXR may be potentially used to improve the efficacy of imatinib in patients with CML.